2006
DOI: 10.1182/blood-2006-03-008839
|View full text |Cite
|
Sign up to set email alerts
|

c-Rel plays a key role in deficient activation of B cells from a non–X-linked hyper-IgM patient

Abstract: Our previous results demonstrated that B cells from a patient (pt1) with non-X-linked hyper-IgM syndrome (HIGM) possess an atypical CD23(lo) phenotype that is unaffected by CD40-mediated activation. To investigate the molecular mechanism underlying defective CD23 expression in pt1 B cells, we used lymphoblastoid cell lines that express LMP1 under the control of a tetracycline-inducible promoter (LCL(tet)). Our analysis revealed that the CD23(lo) phenotype in the pt1-LCL(tet) cells is a direct consequence of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 71 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…Interestingly, rescue from Fas induced apoptosis is normal in these cells, demonstrating the existence of distinct CD40 signaling pathways that are at least in part distinguished by the involvement of c-rel. A similar c-rel associated difference in CD40 signaling has been seen in patients with ectodermal dysplasia and hyperIgM syndrome due to mutations in the NF-κB essential modulator, NEMO, where c-Rel dependent IL4 responses are also impaired19. C-Rel is the only NF-kappaB family member with oncogenic activity and the gene is amplified in some B cell lymphomas.…”
mentioning
confidence: 62%
“…Interestingly, rescue from Fas induced apoptosis is normal in these cells, demonstrating the existence of distinct CD40 signaling pathways that are at least in part distinguished by the involvement of c-rel. A similar c-rel associated difference in CD40 signaling has been seen in patients with ectodermal dysplasia and hyperIgM syndrome due to mutations in the NF-κB essential modulator, NEMO, where c-Rel dependent IL4 responses are also impaired19. C-Rel is the only NF-kappaB family member with oncogenic activity and the gene is amplified in some B cell lymphomas.…”
mentioning
confidence: 62%
“…Of the 27,000 genes assessed, 764 (p = 0.05) displayed differential expression of 1.6-fold or higher. Importantly, we were able to show that both the expression of c-Rel and CD23 ( FCER2 ), which had been previously identified as a bona fide c-Rel target, were decreased on the array [32]. However, there was no difference in the expression of pro-survival genes including Bcl-xL and thus the difference observed at the protein level was likely independent of a direct, c-Rel-specific affect on transcription (see Figure 1C).…”
Section: Resultsmentioning
confidence: 73%
“…Our previous analysis of c-Rel expression in Pt1 and control cells suggested that reduced c-Rel expression was due to translational or post-translational differences [32] . However, additional analyses using multiple primer pairs that targeted both the 5′ and 3′untranslated regions revealed that reduced c-Rel corresponded to a transcriptional defect that resulted in an approximate 3.5-fold decrease in RNA ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise molecular targets by which PTIP mediates its function in B cell signaling remain to be elucidated, we provide multiple lines of evidence in PTIP-deficient B-1a cells and activated B-2 B cells for deregulation of the classical NF-κB pathway. In addition to decreased cREL and increased IκBα at steady state and in response to anti-IgM, we find protein levels of a handful of NF-κB target genes to be decreased in PTIP-deficient B cells, including BCL2, BCLXL ( 27 , 28 ), NFATc1 ( 29 ), uPA, IRF4 ( 30 ), and CD23 ( 31 ). These findings indicate a requirement for PTIP in the classical NF-κB pathway and are in line with ( i ) the established role of the NF-κB pathway in B-1 cell development ( 15 , 24 , 25 , 32 ), ( ii ) evidence for a role of NF-κB downstream of pre-BCR signaling in small pre-B cells ( 28 , 33 36 ), and ( iii ) FO B-2 cell functionality including activation-induced proliferation, survival, antibody production, GC differentiation, and CSR ( 24 26 , 37 ).…”
Section: Discussionmentioning
confidence: 84%